2021
DOI: 10.1038/s41419-021-03674-z
|View full text |Cite
|
Sign up to set email alerts
|

Foxq1 promotes metastasis of nasopharyngeal carcinoma by inducing vasculogenic mimicry via the EGFR signaling pathway

Abstract: In nasopharyngeal carcinoma (NPC), the treatment of tumor metastasis and recurrence is challenging and is associated with poor clinical efficacy. Vasculogenic mimicry (VM) is a new blood-supply model of malignant tumor that is closely related to tumors’ distant metastasis. Our previous study demonstrated that miR-124 could target Foxq1 to inhibit NPC metastasis. Whether Foxq1 affects metastasis through vasculogenic mimicry is worth consideration. In this study, we show that VM formation positively correlates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…Evidence supports that VM structures promote tumor dissemination and metastasis ( 32 ). Furthermore, the formation of VM is strongly associated with the abnormal expression of several miRs, suggesting that miRs are potential targets for anti-VM therapy ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence supports that VM structures promote tumor dissemination and metastasis ( 32 ). Furthermore, the formation of VM is strongly associated with the abnormal expression of several miRs, suggesting that miRs are potential targets for anti-VM therapy ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Periodic acid-Schiff (PAS) staining combining with CD34 immunohistochemistry (IHC) can be used to detect the structure of VM ( 7 ). VM has been shown to be present in various malignant tumors ( 8 ), namely, NPC ( 8 ), which is associated with tumor metastasis ( 9 ) and poor prognosis ( 7 ). Since the structure of VM is composed of cancer cells, the benefit of VEGF-targeted therapy which is focused on ECs is limited and unsatisfied.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of these genes promotes cell cycle progression and the Warburg effect, which enhances the invasion and metastasis ability of NPC cells [72,76]. Moreover, the highly conserved transcription factors Forkhead box Q1 (Foxq1), regulated by miR-124, could directly bind to the EGFR promoter and increase EGFR expression, thereby inducing vasculogenic mimicry via the EGFR signalling pathway to promote NPC metastasis [77,78]. Similarly, the overexpression of LACTB (serine beta-lactamase-like protein) promotes NPC cell motility in vitro and metastasis in vivo, depending on the activation of ErbB3/EGFR-ERK signalling, which is not conducive to the survival of NPC patients [79].…”
Section: Egfr Promotes Invasion and Metastasis Of Nasopharyngeal Carcinoma Cellsmentioning
confidence: 99%
“…Deng et al ( 113 ) suggested that miR-124 was able to radiosensitize glioblastoma multiforme cells by targeting CDK4. In addition, miR-124 has been reported to be downregulated in NPC ( 114 ). miR-124 may enhance cell radiosensitivity by targeting JAMA and PDCD6 ( 105 ).…”
Section: Mirnas Regulating Ferroptosismentioning
confidence: 99%